1979
DOI: 10.1210/endo-105-1-261
|View full text |Cite
|
Sign up to set email alerts
|

Release of Growth Hormone from Purified Somatotrophs: Role of Adenosine 3′,5′-Monophosphate and Guanosine 3′,5′-Monophosphate*

Abstract: Studies were carried out to simultaneously measure cAMP and cGMP accumulation and GH release from acutely dispersed purified somatotrophs obtained from rat adenohypophyses. cAMP accumulation was dramatically increased by both prostaglandin E2 (10(-6) M) and 3-isobutyl-1-methylxanthine (a phosphodiesterase inhibitor, 0.5 mM) within 1 min of their addition, while there was a delay of 8--16 min before a significant increase in GH release was seen. SRIF (100, 10, or 1 ng/ml) completely blocked the stimulated relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…However, the post-receptor events in this cell type are only partially understood so far. Somatostatin has, to a certain extent, an inhibitory CALCIUM CURRENTS AND SOMATOSTATIN4 action on cyclic AMP production (Sheppard, Spence & Kraicer, 1979), but additional mechanisms, such as Ca2+ mobilization, have also been reported (Dorflinger & Schonbrunn, 1983;Sheppard, Moore & Kraicer, 1985;Epelbaum, Enjalbert, Krantic, Musset, Bertrand, Rasolonjanahary, Shu & Kordon, 1987). We have previously shown that somatostatin increased membrane potassium conductance, leading to the hyperpolarization of the membrane potential.…”
Section: Effects Of Pertussis Toxin Pre-treatment On Somatostatin-indmentioning
confidence: 90%
“…However, the post-receptor events in this cell type are only partially understood so far. Somatostatin has, to a certain extent, an inhibitory CALCIUM CURRENTS AND SOMATOSTATIN4 action on cyclic AMP production (Sheppard, Spence & Kraicer, 1979), but additional mechanisms, such as Ca2+ mobilization, have also been reported (Dorflinger & Schonbrunn, 1983;Sheppard, Moore & Kraicer, 1985;Epelbaum, Enjalbert, Krantic, Musset, Bertrand, Rasolonjanahary, Shu & Kordon, 1987). We have previously shown that somatostatin increased membrane potassium conductance, leading to the hyperpolarization of the membrane potential.…”
Section: Effects Of Pertussis Toxin Pre-treatment On Somatostatin-indmentioning
confidence: 90%
“…It has been suggested that cells which are not responsive to SRIF contribute significantly to the basal cAMP level in these preparations, so that small changes in the cAMP concentration in a specific subpopulation of responsive cells cannot be detected (11,12). However, in a preparation of dispersed rat pituitary cells consisting largely of (>90%) somatotrophs, Sheppard et al (19) did not detect any inhibition of basal cAMP concentrations by SRIF. Similarly, in the clonal GH 4 Ci cell line, the lack of effect of SRIF on basal cAMP accumulation cannot be explained by a masking effect of high background cAMP levels contributed by nontarget cell types.…”
Section: Effect Of Forskolin On the Inhibition Of Vip-stimulated Prl mentioning
confidence: 97%
“…There are conflicting reports regarding the effects of SRIF on 1552 DORFLINGER AND SCHONBRUNN Endo • 1983 Volll3«No5 cAMP levels in the anterior pituitary (3,12,(15)(16)(17)(18)(19)(20). Furthermore, SRIF inhibits stimulation of GH secretion by cAMP analogs (21)(22)(23)(24) and phosphodiesterase inhibitors (16,(19)(20)(21)24).…”
mentioning
confidence: 99%
“…At the end of the incubation, the cells were flash frozen in methanol-dry ice and stored at -80 'C for cyclic nucleotide determination. Cyclic AMP was extracted and assayed as previously described (Sheppard, Spence & Kraicer, 1979 Fig. 2.…”
Section: Cyclic Amp Determinationsmentioning
confidence: 99%